1970
DOI: 10.1063/1.1653388
|View full text |Cite
|
Sign up to set email alerts
|

DIRECT OBSERVATION OF SINGLE-DOMAIN SrTiO3

Abstract: A single-domain SrTiO3 crystal is obtained by stressing along the [110] direction at 2°K and is observed optically for the first time. Domain structure under [001] stress is also examined. The importance of understanding the domain structure is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Further, we find that the electrostrictive term should play a minor role, because (1) both AXi a^d Ax 3 were found to be of the same sign, and (2) the value of (q n -q 12 ) x 3s estimated from previous experiments 19 is about 3.7 x 10 4 (T a -T) m/F which is rather small compared with the observed values of AXi. Then, as 2Ax 1 .+ Ax 3 = (* 11 + 2* 12 )<p Sa 2 (10) and ^3 s 2 = 0.22xJ0" 4 (T a~T ) rad 2 for T b <T<T ay lA we obtain t u + 2t 12 = 1.28 x 10 10 rad" 2 m/F. Let us now briefly discuss the dielectric behavior below T b .…”
Section: I-i-i-i-i-|-i-i-i-i-|-i-i-i-i-|-i-i-i-mentioning
confidence: 94%
See 1 more Smart Citation
“…Further, we find that the electrostrictive term should play a minor role, because (1) both AXi a^d Ax 3 were found to be of the same sign, and (2) the value of (q n -q 12 ) x 3s estimated from previous experiments 19 is about 3.7 x 10 4 (T a -T) m/F which is rather small compared with the observed values of AXi. Then, as 2Ax 1 .+ Ax 3 = (* 11 + 2* 12 )<p Sa 2 (10) and ^3 s 2 = 0.22xJ0" 4 (T a~T ) rad 2 for T b <T<T ay lA we obtain t u + 2t 12 = 1.28 x 10 10 rad" 2 m/F. Let us now briefly discuss the dielectric behavior below T b .…”
Section: I-i-i-i-i-|-i-i-i-i-|-i-i-i-i-|-i-i-i-mentioning
confidence: 94%
“…Recently, it was demonstrated that a uniaxial compressive stress can produce a single-domain crystal at low temperatures. 9, 10 We report here dielectric measurements on single-domain crystals produced by this technique.…”
Section: Dielectric Properties Of Srti0 3 At Low Temperatures T Sakumentioning
confidence: 99%
“…Furthermore, it was shown that the direction of the surface cut of the STO crystals can strongly affect the orientation of these structural domains. Whereas for STO with a (001) surface one typically finds a poly-domain state for which the possible orientations of the tetragonal axis appear with nearly equal probablity, for STO with a (110) surface the tetragonal axis tends to be preferentially aligned along the [001] direction 17,19 . The latter may well be related to the anisotropy of the (110) surface 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies of Raman scattering in tetragonal SrTiO 3 , samples with uncontrolled domain structure were studied with laser beams larger than usual domain sizes (often smaller than 5 µm in linear dimension [8][9][10] ). This complicates the interpretation of the polarization dependence of the single-phonon Raman peaks and thus the symmetry assignments of the associated phonon modes.…”
Section: Introductionmentioning
confidence: 99%